„Nem vicc”: A humor szerepe az észak-amerikai indián szuverenitási törekvésekben - Szathmári, Judit (Studia Litteraria, 2016)
Opponents to tribal sovereignty define the notion as a case study of “Indians” wanting to have the cake and eat it too, while for those in favor of self-determination the question is not whether to have the cake and/or eat it, but the sole right of baking the cake. The metaphorical sovereignty cake is comprised of executive, legislative, and judicial layers which further include economic, cultural, and political measures taken by Indian peoples towards the realization of self-determination. The essay aims at exploring how the social, cognitive-perceptual, and emotional modes of humor within and outside Indian Country have been utilized to overcome the discrepancies rooted in the conflicting definitions of sovereignty. The analysis also addresses the issue of perspectives: humor arising from the paradoxical understandings of Indigenous and mainstream views of checks and balances, federal responsibilities, and treaty rights. The events cited demonstrate how American Indian communities employ humor to serve as an in/outgrouping mechanism and a way of social control to maintain community integrity.